Pelatihan penyusunan alat evaluasi berbasis gamifikasi di Kabupaten Bandung Barat - Hutajulu, Masta; Ifat Fatimah Zahro; Siti Chotimah; R. Mekar Ismayani (Abdimas Siliwangi, 2025)
The development of digital technology has driven the need for innovation in learning evaluation systems. One effective innovation is the application of gamification to evaluation tools to increase student engagement and motivation. However, many educators lack the skills to optimally develop gamification-based evaluation instruments. This community service activity aims to improve the skills of educators in West Bandung Regency in developing gamification-based evaluation tools using the Kuis Pintar digital platform. The methods used included needs analysis, development of training modules, workshops, hands-on practice, and evaluation of training outcomes. The results of the activity showed a significant improvement in educators' skills in designing gamification-based evaluation instruments. This training is expected to become a model for developing engaging and effective digital-based evaluations in schools.